European small claims procedure. Lights and shadows of a key process for claiming small debts in the European Union - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Small debts are one of the most common in practice, however, they are the least claimed in court. The European Small Claims Procedure seeks to encourage cross-border debts, even if they are small (from an economic perspective), can be claimed. The possibility of collecting unpaid debts implies a very positive aspect from a social, economic and legal perspective. However, despite the fact that Regulation (EC) 861/2007 establishing the European small claims procedure is not new, since it has been applied since January 1, 2009, the results offered by European studies who have analyzed its impact on cross-border debt claims show that it has been rather scant. One of the reasons is because it has been an unknown tool for its potential users (small businesses and consumers) until relatively recently, but another has to do with its own configuration. About how this process has been conceived by the European legislator (in the initial version and also in the successive modifications) and the problems it raises in practice is what this paper will deal with.
Keywords: Cross-border debt; creditor; debtor; European small claims procedure